Soviet and post-soviet sexualities - Mole, Richard C. M. 1968- (Routledge contemporary Russia and Eastern Europe series, 2019)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of Illustrations -- Figures -- Table -- Notes on Contributors -- Acknowledgements -- 1 Constructing Soviet and post-Soviet sexualities -- Introduction -- Constructing Soviet sexualities -- Constructing post-Soviet sexualities -- Notes -- References -- 2 'Why are we the people we are?' Early Soviet homosexuals from the first-person perspective: new sources on the history of homosexual identities in Russia -- Anonymous voices: the dominant discourses -- From decriminalisation to self-advocacy and back -- Acknowledgements -- Notes -- References -- 3 Between the labour camp and the clinic: tema or the shared forms of late Soviet homosexual subjectivities -- Concepts and methods -- Stigmatisation and the production of shared subjectivities -- Soviet homosexual subjectivities centred on language, irony and solidarity -- Acknowledgements -- Notes -- References -- 4 Soviet legal and criminological debates on the decriminalisation of homosexuality (1965-1975) -- The Soviet anti-sodomy law and Khrushchev's de-Stalinisation -- The Latvian case: attempts to criminalise lesbian sexual activity -- The legal argument for decriminalisation -- The MVD's objections to decriminalisation -- Conclusion -- Acknowledgements -- Notes -- References -- 5 A Cold War for the twenty-first century: Homosexualism vs. Heterosexualism -- Introduction -- Homosexualism -- Heterosexualism -- Boomerang -- Conclusion -- Acknowledgements -- Notes -- References -- 6 'That's not the only reason we love him': Chaikovsky reception in post-Soviet Russia -- Soviet nostalgia and post-Soviet erasure -- Chaikovsky on the Russian Internet: site of resistance or echo chamber? -- The uses of queer biography -- Notes -- References